AN IN VITRO ANALYSIS AND ETHNOBOTANICAL PROFILE OF JASMINUM SAMBAC L. (International Association of Biologicals and Computational Digest, 2022)
The use of herbal drugs for prevention and treatment of various health ailments has been in practice since time immemorial. The main beauty and uniqueness of jasmine is its fragrance, which cannot be imitated by any known synthetic aromatic chemical and has a unique status in the perfume world. Apart from that inhaling Jasmine scent increases beta waves in the brain, which are associated with increases states of alertness. Various diseases like conjunctivitis, diarrhoea, abdominal pain and dermatitis are treated with its flowers along with roots and leaves are also utilized for curing pain, diarrhoea and fever. The present research is the highlight of various traditional uses as well as in vitro analysis reported till date from J. sambac. Regeneration of Maid of Orleans through direct and indirect organogenesis has been investigated.
Keywords: Organogenesis, in vitro, ethnobotanical